OUTCOMES IN EARLY RESPONDERS ACHIEVING ≥5% WEIGHT LOSS AT 16 WEEKS WITH LIRAGLUTIDE 3.0 mg AS AN ADJUNCT TO INTENSIVE BEHAVIOUR THERAPY (IBT) IN INDIVIDUALS WITH OBESITY IN THE SCALE IBT TRIAL - Wadden, Thomas; Auerbach, Pernille; Endahl, Lars; Tronieri, Jena Shaw; Skovgaard, Dorthe; Sugimoto, Danny; Rubino, Domenica; Shoeb, Ahsan (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The SCALE IBT study demonstrated the overall efficacy of liraglutide 3.0 mg for weight reduction as an adjunct to IBT. The present analysis explored the effect of intervention in the subgroup of liraglutide-treated individuals categorized as early responders (ER) who lost ≥5% at week 16. This subgroup corresponded to individuals that would have been eligible to continue treatment after 16 weeks in a realworld clinical setting. METHODOLOGY The 56-week SCALE IBT trial randomized adults with obesity (BMI ≥30 kg/m²) and without diabetes to liraglutide 3.0 mg or placebo as an adjunct to a Centers for Medicare & Medicaid Services-based programme of IBT (CMS-IBT), including prescribed exercise (escalating to 250 min/week) and diet (1200–1800 kcal/day). This exploratory post-hoc analysis assessed the proportion of liraglutide-treated individuals categorized as ER and describes their outcomes after 56 weeks of treatment. RESULTS AND DISCUSSION Mean characteristics at randomisation (n=142) for liraglutide 3.0 mg-treated individuals were: 45.4 years old, 83.8% females, 109 kg, BMI 39.3 kg/m².At 16 weeks, 66.9% of these had achieved ≥5% weight loss. At 56 weeks, mean weight reduction in this ER subgroup was 10.4%, with 79.9% and 44.2% of this subset achieving weight loss ≥5% and ≥10%, respectively, and 88.4% of this subset still on drug. Other secondary outcomes are shown in the table. Adverse events were similar in the ER subset to the overall trial population, the most frequent adverse events were gastrointestinal events reported for 74.7% in the ER subset as compared with 71.1% in the overall liraglutide group and 48.6% in the overall placebo group. CONCLUSION More than two-thirds of people with obesity receiving liraglutide 3.0 mg as an adjunct to IBT were eligible for long-term treatment according to the EMA prescribing information. Of these, the majority continued on therapy to 56 weeks achieving clinically relevant reductions in body weight.